DISCOVERY LEARNING AS A METHOD TO TEACH DESCRIPTIVE TEXT IN BUILDING STUDENTS’ CHARACTER: A CASE OF SEVENTH GRADE STUDENTS OF SMP N 3 ULUJAMI - Dwiningsih Feriyanti (Universitas PGRI Semarang, 2014)
Discovery learning is a method which recomended in 2013 curriculum. This method allows the students to seek the information and construct their knowledge by doing some activities. Since 2013, Indonesia conducted new curriculum. There are three recommended methods in this curriculum including Discovery learning.Discovery learning is the suitable method in 21th century. The studentsmust be active learners. This method not only make the students academic enhanced but also this method can make the students have a good attitude by doing all the process of using this method in teaching and learning process. The students was very enthusiatic learning using discovery learning.Learning using Discovery learning continuosly could help the students in building their character